A aventura cinema: imaginários e desenvolvimento profissional docente - Costa, Sabrina Copetti da (2023)
This master's thesis is part of the Programa de Pós-Graduação em Educação of the Universidade Federal de Santa Maria (UFSM) and is aligned with the research line: Teaching, Knowledge, and Professional Development. The primary theoretical framework for this study is Cornelius Castoriadis' Theory of Social Imaginary, with the main objective of approaching the imaginaries of teachers who participated in cinema projects, specifically within the Grupo de Estudos e Pesquisas em Educação e Imaginário Social (GEPEIS) at the Universidade Federal de Santa Maria. The aim was to construct an understanding of the relationship between participation in these projects and the potential learning and unlearning experiences for the professional teacher development (PTD) of these individuals.A qualitative research approach, inspired by the Research-formation framework (JOSSO, 2010), was employed, wherein the exploration of imaginaries utilized oral and filmic autobiographical narratives as investigative tools. To what extent might this participation have been formative in the educational journey of the teachers? This question guided the writing of this master’s thesis. Among the teachers who had previously participated in GEPEIS's cinema projects, three female pedagogues were randomly selected. During this research-formation, they participated in five Conversational Rounds (four in-person and one virtual) inspired by the Wheel and Record methodology (WARSCHAUER, 2017). Additionally, they were invited to create, based on a film exercise called Minuto Alice Guy-Blaché, later screened to the group. The teachers recounted formative teaching experiences transformed by aesthetic encounters with the seventh art through GEPEIS projects, sharing practices that emphasize sensitivity, enchantment, and imagination. This approach transcends reductionist educational projects that only consider rational aspects of training.The three teachers expressed a significant appreciation for and incorporation of art into their work in schools. Other constructed outcomes included the expansion of filmic repertoires and formative perspectives on schools, children, and professional teacher development.